2015
DOI: 10.1007/s10549-014-3257-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical outcomes in women with breast pain in the absence of additional clinical findings: mammography remains indicated

Abstract: The purpose of the study was to determine the long-term clinical outcomes of women with breast pain in the absence of additional symptoms or signs (isolated breast pain), and the utility of mammography in their work-up. IRB approved, HIPAA compliant study retrospectively reviewed 1,386 patients referred for breast imaging with ICD-9 code for breast pain between 1/1/2006 and 12/31/2007. Of these, 617 consecutive women (mean age, 49 years) with isolated breast pain, mammogram, and follow-up (mean, 51 months) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Based on our clinic data and previous reports 25 , it was assumed that women presenting with pain only and diagnosed with breast cancer had early-stage disease, received treatment and then, after 52 weeks, returned to general population levels of health utility. As a worst-case scenario, for women with cancer not referred to breast clinic, it was assumed that they had equivalent health utility to women with early-stage cancer for 52 weeks, and then late-stage cancer for 52 weeks, after which they died.…”
Section: Utility/quality-adjusted Life Years (Qalys)mentioning
confidence: 98%
See 1 more Smart Citation
“…Based on our clinic data and previous reports 25 , it was assumed that women presenting with pain only and diagnosed with breast cancer had early-stage disease, received treatment and then, after 52 weeks, returned to general population levels of health utility. As a worst-case scenario, for women with cancer not referred to breast clinic, it was assumed that they had equivalent health utility to women with early-stage cancer for 52 weeks, and then late-stage cancer for 52 weeks, after which they died.…”
Section: Utility/quality-adjusted Life Years (Qalys)mentioning
confidence: 98%
“…Seven of 8 studies in the past 10 years note rates of 0-0.4% 8 with the small numbers of malignancies seen being in women above 40 years 12 25 37 . Some suggest that symptoms of non-cyclical focal breast pain may be associated with higher incidence of breast malignancy 25 than other presentations of breast pain. However, this is inconsistent and not been noted by others [36][37][38][39] .…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…These publications included patients across nine decades of life (range 12-92 years of age) presenting with breast pain only. [10][11][12][13][14][15][16][17][18][19][20][21] Six thousand two hundred and fiftyseven patients were identified with breast pain only across 13 studies. Twenty-nine cancers were identified in this group (0.46%), or equivalent to 4.6 per 1000 patients.…”
Section: Literature Reviewmentioning
confidence: 99%
“…4 Breast cancer does not generally cause cyclic breast pain, and studies have not identified a causative relationship between symptoms and breast cancer risk. 5 Noncyclic Breast Pain Noncyclic breast pain tends to be more focal than cyclic breast pain and is often limited to a specific quadrant of the breast, although the pain may be diffuse. In contrast to patients with cyclic breast pain, patients with noncyclic pain are typically older, with the age of onset in the 40s to 50s.…”
Section: Cyclic Breast Painmentioning
confidence: 99%